2007
DOI: 10.1142/s1084946707000769
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Entrepreneurship: Studying Chinese and Indian Students in the United States

Abstract: Current literature has not touched upon the topic of entrepreneurial intention among international students. Using the theory of planned behavior as a theoretical framework, this study addresses this gap by looking at the entrepreneurial intentions of Chinese and Indian students at a top university located in the Midwest United States. This study also explores their perceived barriers of being entrepreneurs in the United States and expected help from the university. Both survey and interviews are used for data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 11 publications
2
35
0
1
Order By: Relevance
“…While the social norms element is also thought to influence entrepreneurial intentions, several empirical studies (e.g. Krueger et al, 2000;Li, 2007) have found little evidence of this. Consequently, we align our study with the predominant view that entrepreneurial intentions are seen as a function of perceived desirability and perceived feasibility.…”
Section: Entrepreneurial Intentions Modelsmentioning
confidence: 99%
“…While the social norms element is also thought to influence entrepreneurial intentions, several empirical studies (e.g. Krueger et al, 2000;Li, 2007) have found little evidence of this. Consequently, we align our study with the predominant view that entrepreneurial intentions are seen as a function of perceived desirability and perceived feasibility.…”
Section: Entrepreneurial Intentions Modelsmentioning
confidence: 99%
“…Thus, it is also hypothesized that: Moreover, Scherer et al (1989), Matthews and Moser (1995) and Trivedi (2016) Choo and Wong (2006) believe that very few empirical studies have analyzed cognitive barriers faced by potential entrepreneurs in starting their venture. Li (2007) asked researchers to link entrepreneurial intention with the barriers faced by potential entrepreneurs. These studies may lead to understanding students' needs during their university years.…”
Section: Entrepreneurial Intention Among Studentsmentioning
confidence: 99%
“…The issue of language familiarity has not been addressed. Indians immigrants, as compared to the Chinese immigrants, are on an average better versed in the English language, and see language as less of a problem (Li, 2007). This has important implications for their dealings with the dominant community, and affects the rate and relative success at which they can interact with it.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%